Multicarrier demodulation for frequency selective channels subject to narrow band interferences - Jajamovich, Guido H.; Galarza, Cecilia G. (Digital signal processing, 2008)
Nowadays, multicarrier modulation (MCM) systems based on the discrete Fourier transform are commonly used to transmit over frequency selective channels subject to aggressive noise disturbances. However, these transceivers suffer from poor subchannel spectral containment, that is, the level of inter-channel interference is not negligible. It can be shown that the system performance decreases when it is subject to a disturbance with most of its energy concentrated on a narrow frequency band. To improve the quality of service under these conditions, we present general MCM systems based on filter bank transformations. Lately, we add an equalizer at the channel output to implement these techniques over frequency selective channels, and we introduce a set of design strategies for the equalizer. Finally, we evaluate the performance of the overall system by simulating a frequency selective channel subject to narrow band interference.